Perbandingan Model Pembelajaran Discovery Learning dan Model Pembelajaran Langsung terhadap Hasil Belajar Peserta Didik Kelas X P.Mia SMA Negeri 1 Parangloe (Studi Pada Materi Pokok Ikatan Kimia) - Syafriyanto, Muhammad; Danial, Muhammad; Yunus, Muh. (ChemEdu, 2023)
The research was a quasi-experimental that aimed to know the difference discovery learning and direct learning of student’s achievement in class X P.Mia Senior High School 1 Parangloe. The study design used is posttest only control group design. The population was class X P.Mia Senior High School 1 Parangloe which consisted of 102 students from three classes. The class selected as a sample was class X P.Mia 2 which consisted of 35 students as an experimental 1 class and class X P.Mia 1 which consisted of 31 students as an experimental 2 class. Experimental 1 class taught using discovery learning whereas experimental 2 class taught using direct learning. The independent variable in this research was discovery learning and direct learning, whereas the dependent variable was student’s achievement. Data collection technique was obtained that giving test the student’s achievement for posttest. Results of inferential statistical analysis prerequisite test showed that the data were not normally distributed. Testing the hypothesis with Mann Whitney test conducted by α = 0,05 were Zcalculated= 2,155 > Ztable = 1,96. Conclude that there are difference of discovery learning and direct learning of student’s achievement in class X P.Mia Senior High School 1 Parangloe in.